Perancangan Sistem Monitoring Tukang Parkir Liar secara Real-Time Menggunakan YOLOv11 - Ashari, Imam Ahmad; Hidayat, Rachman; Wulandari, Annastasya Nabila Elsa; Arkananta, Edgina Rangga; Trivilia, Indah (Universitas Harapan Bangsa, 2025)
The widespread presence of illegal parking attendants in various urban areas has caused serious problems in terms of traffic order, public safety, and potential economic losses. Illegal parking attendants often create traffic congestion, increase the risk of criminal activity, and cause inconvenience for road users. This situation demands a technology-based solution capable of performing monitoring and detection quickly and accurately. This study proposes the design of a real-time monitoring system for illegal parking attendants by utilizing You Only Look Once (YOLOv11). The YOLOv11 algorithm was selected due to its ability to detect objects with high accuracy and optimal processing speed. The system is designed with the integration of Closed-Circuit Television (CCTV) cameras directly connected to the YOLOv11 detection model, enabling automatic surveillance of public areas. The detection results can be processed and displayed in real time, facilitating authorities in taking appropriate actions. With this system, it is expected that the supervision of illegal parking activities can be carried out more efficiently, while also providing a significant contribution to improving security, order, and comfort in urban public spaces.